2018
DOI: 10.1007/s11916-018-0689-1
|View full text |Cite
|
Sign up to set email alerts
|

Global Supply and Demand of Opioids for Pain Management

Abstract: The total global production of opium for opioid manufacturing is enough to supply the growing global demands. However, licit opioids are only consumed by 20% of the world population. Most people throughout the world had no access to opioid analgesics for pain relief in case of need. Opioid misuse and abuse is not only a phenomena plague by the USA but globally across many countries. Many countries have a lack of availability of opioids, contributing factors being strict government regulations limiting access, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Despite the fact that global demand for opioids has increased significantly in the past 20 years (1), the international availability and acceptability of opioids for pain management varies considerably. A recent study reported that the majority of the world’s population has insufficient access to opioids for pain management (2, 3), with only 7.5% of people having adequate opioid access and 66% of people having little to no access (4). Some of the myriad reasons for limited opioid access include differences in provider practices and healthcare system operations, financial barriers, cultural beliefs regarding pain management, and/or variations in opioid-related regulations (57).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that global demand for opioids has increased significantly in the past 20 years (1), the international availability and acceptability of opioids for pain management varies considerably. A recent study reported that the majority of the world’s population has insufficient access to opioids for pain management (2, 3), with only 7.5% of people having adequate opioid access and 66% of people having little to no access (4). Some of the myriad reasons for limited opioid access include differences in provider practices and healthcare system operations, financial barriers, cultural beliefs regarding pain management, and/or variations in opioid-related regulations (57).…”
Section: Introductionmentioning
confidence: 99%
“…When providers in other countries did prescribe outpatient medications for pain, it was more likely to be acetaminophen or ibuprofen first, followed by less potent opioids like tramadol. This difference in prescribing habits could be due to more availability of opioids in the US as evidenced by the fact that the US is one of the nations that consumes the highest percentage of the world's opioids [18] or because US physicians were more comfortable prescribing opioids. However, this difference in practice is very important to explore as it relates to overall outcomes in SCD, frequency of acute care utilization, and quality of life for affected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In Canada, prescription opioid analgesics (POAs) increased in all provinces from 2005 to 2011 [3]. More than 90% of licit morphine is used by roughly 20% of the global society, primarily in the US, Canada, Germany and Australia, and approximately 66% of the world' s population have almost no access to opioids, despite having a high disease burden from conditions and illnesses known to cause pain [4]. Increased access to POAs in the US and Canada has done more than treat pain-it has spurred a regional epidemic of opioid-related deaths.…”
Section: The Opioid Crisis In North America: Causes and Impactsmentioning
confidence: 99%